Clinical value of neutrophil-to-lymphocyte ratio as a predictor of prognosis of RetroNectin®-activated cytokine-induced killer cell therapy in advanced non-small-cell lung cancer. (14th December 2018) - Zhao, Lingdi; Li, Tiepeng; Yang, Yonghao; Zhang, Yong; Li, Wei; Han, Lu; Shang, Yiman; Lin, Hongwei; Ren, Xiubao; Gao, Quanli
Aim: To assess the impact of neutrophil-to-lymphocyte ratio (NLR) on time to progression (TTP) and overall survival (OS) and explore the value of NLR as an indicator in patients with non-small-cell lung cancer (NSCLC) treated with RetroNectin ® -activated cytokine-induced killer (R-CIK) cells.Patients & methods: Using data gathered from a single center between January 2010 and June 2015, 201 patients with stage IIIB or IV NSCLC receiving at least four cycles of R-CIK cell therapy were included. Univariate and multivariate Cox regression analyses were performed to evaluate the associations of NLR with TTP and OS.Results: The pretreatment NLR was correlated with TTP and OS. Multivariate analysis showed that NLR was an independent factor for survival.Conclusion: NLR was an independent indicator to predict benefit from R-CIK-based combination therapy.